FOSTERING HARMONIOUS SOCIETAL CONSTRUCTS THROUGH ISLAMIC PRINCIPLES - Bello Ali (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
The paper underscores the profound impact of Islamic principles in promoting understanding, unity, and peaceful coexistence within societal constructs. Drawing from various facets of Islamic teachings deeply rooted in the Qur'an and the Prophet's guidance, the study advocates for compassion, justice, and inclusivity in societal construction. The convergence of these principles serves as a beacon for fostering coexistence and justice, offering pathways to construct harmonious societies. Following an extensive exploration of inter-group relations in the region, the study proposes a set of recommendations to address challenges and cultivate lasting harmony. These recommendations encompass initiatives such as education and awareness programs to bridge gaps, community-based conflict resolution mechanisms, advocacy for inclusive governance, support for interfaith dialogue and collaboration, civic engagement and empowerment, enhanced security measures, collaboration with NGOs and international bodies, media sensitization campaigns, incorporation of Islamic perspectives into education and outreach, and continual research for adaptive strategies and effectiveness monitoring. The implementation of these recommendations is envisioned to create an environment conducive to peaceful coexistence, understanding, and shared prosperity within Nigeria, particularly Taraba State.